Smartphone application for physical activity enhancement at workplace: would office workers actually use It? - Mohd Mohadis, Hazwani; Mohamad Ali, Nazlena (The Institute of Electrical and Electronics Engineers, Inc., 2018)
The proliferation of smartphone into daily life could potentially become an effective medium for the delivery of workplace-based physical activity intervention. Based on Unified Theory of Acceptance and Use of Technology model (UTAUT), this study investigates factors influencing office workers’ intention to use smartphone application to enhance their physical activity at workplace. A total of 195 valid surveys were collected and subsequently analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM) approach. The outcome demonstrated that both Performance Expectancy (PE) and Social Influence (SI) have significant positive effect on Behavioural Intention. Effort Expectancy (EE) in contrast has no significant influence on office workers’ intention to use. This study provides a preliminary evidence on factors that should be consider by researchers, developers and employers in developing smartphone applications aiming to enhance physical activity at workplace among office workers.